Repercusión del aumento de la periodicidad de las reuniones en las que el equipo del Programa de Optimización del Uso de Antimicrobianos realizó auditorías no impositivas de ayuda a la prescripción en el consumo de antimicrobianos - Inmaculada Zas-García, María; Manuel Fernández-Carreira, José; Rodríguez-Prida, Jorge; Blanco-Suárez, Ana; Álvarez-Pérez, Marcos; Rubio-Sanz, Jesús; Castelo-Álvarez, Elsa; González-Fernández, Daniel; Rubio-Alfonso, Tania (Revista Española de Quimioterapia, 2026)
Objective. To evaluate how antimicrobial consumption was influenced by increasing the frequency of meetings in which the Antimicrobial Stewardship Program (ASP) team conducted prospective audit and feedback (PAF). Materials and methods. Retrospective cohort study comparing consumption in DDD per 1000 beds-day and DDD per 1000 admissions across groups of anti-infectives, antibacterial groups, agents against methicillin-susceptible Staphylococcus aureus (anti-MSSA agents)/agents against methicillin-resistant Staphylococcus aureus (anti-MRSA agents), antibiotics targeting sensitive Gram-negative bacteria/antibiotics targeting resistant Gram-negative bacteria and antimicrobial agents, during two comparative periods of ASP activity (2 weekly meetings in 2023 versus 1 weekly meeting in 2022). Results. Comparing 2023 to 2022: antibacterials for systemic use consumption increased in DDD per 1000 beds-day (+0.13%) and decreased in DDD per 1000 admissions (-3.55 %); consumption in DDD per 1000 beds-day and DDD per 1000 admissions increased for penicillins, glycopeptides and aminoglycosides while it decreased for cephalosporins and carbapenems, quinolones use increased per beds-days but decreased per admissions; regarding anti-MSSA and anti-MRSA agents, consumption of cefazolin, cloxacillin, vancomycin and daptomycin increased in DDD per 1000 beds-day and DDD per 1000 admissions, linezolid consumption increased per beds-day but decreased per admissions; for antibiotics targeting sensitive Gram-negative bacteria and antibiotics targeting resistant Gram-negative bacteria, consumption of amoxicillin-clavulanate, piperacillin-tazobactam, aminoglycosides, ceftazidime, cefepime and polymyxins increased per DDD/1000 bed-days and DDD per 1000 admissions, carbapenems consumption decreased per bed-days and admissions. Conclusions. The increase in the frequency of meetings seems to be related to better use of antimicrobials in our center.